B Cell Modulation Strategies in Autoimmune Diseases: New Concepts - Musette, Philippe; Bouaziz, Jean David (Frontiers in Immunology, 2018)
B cells are major effector cells in autoimmunity through antibody production, T cell help and pro-inflammatory cytokine production. Major advances have been made in human B cell biology knowledge using rituximab and type II new anti-CD20 antibodies, anti-CD19 antibodies, anti-CD22 antibodies, auto-antigen specific B cell depleting therapy (chimeric antigen receptor T cells) and B cell receptor signaling inhibition (ibrutinib). However, in certain circumstances B cell depleting therapy may lead to the worsening of the autoimmune disease which is in accordance with the existence of a regulatory B cell population. Current concepts and future directions for B cell depletion in autoimmune diseases are discussed.